ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMK DI KOTA CIMAHI PADA MATERI GEOMERTRI RUANG - Nina Lestari; Luvy Sylviana Zanthy (IKIP Siliwangi, 2019)
This study aims to determine the ability of mathematical creative thinking of students in one of the Vocational Schools in Cimahi City with indicators of students' mathematical creative thinking skills used are fluency, flexibility, originality and elaboration. The ability to think creatively mathematically is the ability to learn mathematics in finding new ideas or ideas that are different from the way, in their own language. This research was conducted on 29 students in one of the Vocational Schools in Cimahi City using qualitative descriptive methods. The instruments used were in the form of 4 items of description with mathematical creative thinking skills in space geometry. After getting the results or data, then the data is presented in the form of a percentage. And it can be concluded from this study that the ability of mathematical creative thinking of SMK students in Cimahi City is still very low because only one indicator whose percentage exceeds 50% is an indicator of fluency. The results of this study can increase knowledge about mathematical creative thinking of students in one of the Vocational Schools in Cimahi City and is useful to facilitate education practitioners in developing mathematical creative thinking skills